The effectiveness of UMKM tax collection at the west Makassar primary tax office - Sudirman abdi; Azwar Wijaya Syam (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
“The effectiveness of UMKM tax collection at the west Makassar primary tax office”. The research published o/n the final project is aimed at recognizing the effectiveness of UMKM tax collection on western Makassar primary tax services.The type of research used is qualitative descriptive that writing describes the results of observation and analyses data obtained in the freld. Writing thefinal task is the result of research performed in May 2020 to june 2020.After analyzing and discussing a problem,The authors have concluded that bthe effectiveness of umkm tax collection in the western makassar primary tax service.The effectiveness of umkm’s application is not particularly effective because it is linked to the number of tax enlistments and the number of taxpayers malking payments based on PP 23 in 2018 the tax revenues from the tax were divided into two sectors of their own and out or collected by the later.